Spindle Cell Lipoma Occurring in the Buccal Mucosa: An Unusual Location of This Benign Lipomatous Neoplasm - Noala Vicensoto Moreira Milhan; Ana Sueli Rodrigues Cavalcante; Yonara Maria Freire Soares Marques; Yasmin Rodarte Carvalho; Ana Lia Anbinder (Case Reports in Pathology)
Spindle cell lipoma is a benign lipomatous neoplasm, which rarely occurs in the oral cavity. The aims of this paper are to report a case of spindle cell lipoma located in buccal mucosa and discuss the main clinical, histological, and immunohistochemical findings of this entity. Thus, we report a 4-year history of an asymptomatic smooth surface nodule in an elderly Caucasian man with clinical hypothesis of fibroma. The histopathological examination showed spindle cells, mature adipose tissue, and many mast cells in a stroma of connective tissue presenting ropey collagen fibers bundles. After immunohistochemical analysis, the final diagnosis was spindle cell lipoma.